SUBKULTUR GRUNGE (ANALISIS KRITIS TENTANG KONSTRUKSI REALITAS SOSIAL DAN KESADARAN KRITIS MUSISI GRUNGE DI KOTA SURABAYA) - Puji Laksono; Drajat Tri Kartono; Argyo Demartoto (Jurnal Analisa Sosiologi, 2015)
Subculture born from rock subcode frequently creates a counterculture of the mainstream. In fact, subculture of grunge shows its counterculture side through its resistance against capitalism, such as grunge offers new freedom to provide platforms for its followers to put forth their idealism, anger, disappointment towards the surroundings, politics, and social matters. The purpose of this study is to determine how the construction of social reality, such as the freedom, and resistance as well as critical consciousness of grunge subculture in Surabaya. The research was conducted to the grunge musicians in Surabaya. This study uses phenomenology method consisting of the object, meaning, experience, and consciousness from the grunge musicians’ perspectives. The theory used is the theory of social reality construction of Peter L. Berger and Thomas Luckmann, combined with the critical theory ─ the theory of music from Theodor W. Adorno. Data were collected through direct observation and in-depth interviews. The validity of the data was done by using triangulation.The findings show that the grunge musicians tend to choose grunge as their music genre because it has motivation referring to the past and the future. The factors underlied their selection of grunge genre are the lack skill of music, the influence of the association, and also the influence of the close friends or family. The purpose their selection of grunge genre are to share their hobby in music and to share aspirations. The grunge musicians construct the freedom within the characteristic aspect of musicality in which its musicians are not required to have high skills in music due to no strick standard, a performance style that shows simplicity, and also the ethics of “Do It Yourself (DIY)” which shows the attitude of self-reliance. The freedom in subkultur grunge which formerly was known as a form of resistance, indeed it is not. In fact, not all musicians interpret the freedom in grunge as a resistance. From various interpretations upon this resistance,  the grunge musicians can be categorized into three kinds, namely resistance grunge musicians, subjective-resistance grunge musicians, and non-resistence grunge mucisians. Encountering some objective structures like the music industry and socio-politic matters, the grunge musicians have found their consciousness dimensions. Those dimensions include magical, naive, and critical consciousness. Through the grunge musicians who have critical consciousness, grunge genre becomes social media criticism.Keywords: Subcultures, Grunge, Critical consciousness, Social reality.